PEREMPUAN MINANGKABAU DALAM NOVEL HARTA PUSAKA CINTA KARYA DESNI INTAN SURI - Musfeptial NFR (Balai Bahasa Sulawesi Tengah, 2020)
This paper is entitled Minangkabau Woman in Novel Harta Pusaka Cinta by Desni Intan Suri. The aim of this research is to describe the Minangkabau ideal female character in the novel. The theory used is the character theory of characters in literary works and the theory of cultural preservation. This research uses descriptive method. Data analysis showed that there were three different characters, namely Andung Rabiah, Friska Aisyaharni and, and Chintiya Rubert. Culturally the three are Minangkabau women. Andung Rabiah figure who was born and raised in the colonial era with a strong foundation of religious and customary education, so there is a balance between world science and the afterlife. It was different only with the figure of Friska Aisyaharni, she felt that the religious lessons she had received and the cultural life of the traditional jointed religion she received was considered by Friska as the fetter of the freedom she wanted. In the meantime, Chintiya Rubert who was born with a very secular western culture actually got his identity when he met his grandmother in Ampek Angkek.Keywords: female, ideal, minangkabau.